2010
DOI: 10.1089/lrb.2009.0011
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Pump Treatment Mobilizes Leukocytes from the Gut Associated Lymphoid Tissue into Lymph

Abstract: LPT mobilizes leukocytes from GALT, and these leukocytes are transported by the lymphatic circulation. This enhanced release of leukocytes from GALT may provide scientific rationale for the clinical use of LPT to improve immune function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 22 publications
8
46
0
Order By: Relevance
“…Therefore, the objective of this study was to develop a rat model to determine if experimental LPT would increase lymph flow and leukocyte concentration as observed in dogs. 14,15 Our results show that LPT increases the flux of lymphocytes in the cisterna chyli (CC) of rats, thus demonstrating that this treatment produces similar effects in two distinct mammalian models. Furthermore, we have developed a small animal model to investigate the effects of LPT on the lymphatic and immune systems.…”
mentioning
confidence: 69%
See 3 more Smart Citations
“…Therefore, the objective of this study was to develop a rat model to determine if experimental LPT would increase lymph flow and leukocyte concentration as observed in dogs. 14,15 Our results show that LPT increases the flux of lymphocytes in the cisterna chyli (CC) of rats, thus demonstrating that this treatment produces similar effects in two distinct mammalian models. Furthermore, we have developed a small animal model to investigate the effects of LPT on the lymphatic and immune systems.…”
mentioning
confidence: 69%
“…15 Therefore, to determine if LPT mobilizes GALT derived lymphocytes into the CC of rats, we stained lymphocytes collected from the CC for the gut homing leukointegrin a4b7. 16 Approximately 40% of the lymphocytes in the CC stained positive for.…”
Section: Lpt Mobilizes Gut-associated Lymphocytes Into CC Lymphmentioning
confidence: 99%
See 2 more Smart Citations
“…Lymphatic pump techniques have been shown to increase cytokines and chemokines in thoracic and intestinal lymph vessels 35 , while mechanical pressure to certain body regions distant from the location of lymph formation enhances flow into lymphatic systems 36 . In addition, it has been shown that lymphatic OMT augments leukocyte mobilization and flow in dogs and rats, primarily from gut-associated lymphoid tissue 37,38,39,40,41 .…”
Section: Representative Resultsmentioning
confidence: 99%